Karakteristik Pendidik Rahmani dalam Surah ar-Rahman : (Kajian Pustaka: Tafsir Tematik) - Zahra, Mufrida; Hadiyanto, Andy; Siregar, Khairil Ikhsan (Jurnal Studi Al-Qur’an, 2020)
This study aims to determine the character of rahmani educators in surah ar-Rahman by analyzing thematic interpretations of these verses. Humans are creatures that can not be separated from education, namely as educational actors both as educators and students. Educators are one important component in the education process, because on their shoulders a very large responsibility to take students towards the educational goals to be achieved. In this modern era, there are many people who work as teachers, but many do not understand and implement what competencies must be possessed by an educator. In surah ar-Rahman there are several concepts of educators, including: educators who have a compassionate personality, educators must be knowledgeable, educators who can develop the potential of their students, and educators who have the ability to interact. Keywords: characteristics, rahman educators, thematic interpretations